The interplay between increased tooth crown‐height and chewing efficiency, and implications for Cervidae evolution. (29th July 2015) - DeMiguel, Daniel; Azanza, Beatriz; Cegoñino, José; Ruiz, Inmaculada; Morales, Jorge
Abstract : Mammals of numerous lineages have evolved high‐crowned (hypsodont) teeth particularly during the last 20 million years. This major phenotypic change is one of the most widely studied evolutionary phenomena in a broad range of disciplines, though the mechanisms underlying its transformation remain unresolved. Here, we present the first Finite Element Analysis (FEA) to investigate the alternative hypothesis that there is a biomechanical link between increased hypsodonty and a more effective mastication in deer. Our FE experiments compared patterns of stress and strain within and between different fossil and living species under different loading conditions, and found that more hypsodont teeth are suited for restricting stresses to those areas where chewing loading occurs. This mechanical improvement is consequence of specific and pronounced variations in tooth geometry and morphology of the occlusal surface that are strongly related to crown growth in the vertical plane. We demonstrate that hypsodonty enables selenodont‐teeth to adopt a mechanically improved design that increases the pressure whilst shearing foods. As ruminants are physiologically limited by both the quantity of food consumed and the time spent in the mastication and digestion, hypsodonty is highly advantageous when feeding on mechanically resistant, tough and fibrous foods. Consequently, it allows grass‐eaters to spend less time chewing, thereby increasing the volume of food ingested and/or providing more time for digestion. This study provides a promising line of evidences in support of biomechanical effectiveness, in addition to or instead of increased wear resistance, as a factor in explaining the evolutionary origins of the hypsodont phenotype.